Time since deposition of biological fluids using RNA degradation. Issue 1 (December 2019) - Bird, Thomas Anthony George; Walton-Williams, Laura; Williams, Graham
Abstract: In criminal casework where sexual intercourse has taken place, body fluids are usually left behind. Body fluid identification (BFID) of the type and origin can provide important information regarding what has occurred and who from, however BFID struggles to determine time since deposition (TSD) of biological stains. According to the Crime Survey in England and Wales in 2017, it shows that the majority of sexual offences that occur are committed by people already known to the victims, roughly around 90%, with 56% of these being committed by partners or ex partners. In these cases, the defence is that their DNA will be present because they are in a relationship or were in a prior relationship. To challenge this defence, the degradation of RNA in semen stains could potentially provide information regarding when a stain was deposited. The degradation pattern of a few semen specific mRNA genes and housekeeping genes were evaluated over a 1 month period. These semen stains were extracted periodically and quantified using qPCR generating real-time levels of RNA which can then be compared to the levels of fresh semen. This study shows that different semen specific primers will degrade at different rates over a period of time and therefore could be used to determine the time since deposition of biological fluids.